BOOK REVIEW: FUNDAMENTALS: TEN KEYS TO REALITY - Dieorditsa, Taiana; Tolmachov, Volodimir (Physical and Mathematical Education, 2023)
The author, the Nobel laureate Dr. F. Wilczek, considers the fundamentals of modern physics, which provide an essential structure for how the universe works, and also suggests how humanity fits into the frame. After reading the popular science book «Fundamentals: Ten Keys to Reality», we were convinced that physics as a science is able to teach not only to think, but also to wonder. And the ability to wonder opens our minds to new possibilities and awakens creativity.